Introduction to algorithms - Cormen, Thomas H.; Leiserson, Charles E.; Rivest, Ronald L. (Cambridge, MA : MIT Press, 1990)
This book is about: mathematical foundations; Sorting and order statistics; Data structures; Advanced design and analysis techniques; ...
Keywords: Computer programming; Computer algorithms; Computer programming -- Computer algorithms